ANALISIS LAJU KOROSI ROOFTOP TANGKI 100 KL YANG TERPAPAR LANGSUNG DENGAN AIR LAUT DI PLTD NAMLEA KABUPATEN BURU - Wendy Juita Papilaya; Erwin B, Pattikayhattu; Deny Ismail Pellu; Hendrik S Latumaerissa (Department of Mechanical Engineering, 2024)
Indonesia, as a tropical country surrounded by water, faces serious corrosion problems due to high rainfall and the presence of seawater containing corrosive salts. Metal materials, especially in storage tanks in the oil and gas industry, are very susceptible to this damage, so they require special attention to maintain their integrity.To evaluate the condition of the tank, an inspection was carried out using the Non-Destructive Testing (NDT) method with an Ultrasonic Thickness Gauge according to API 653 and 575 standards. In the August 2024 measurement, the 100 kl tank showed good condition with varying thicknesses. However, the rooftop section, despite having the highest thickness, recorded a higher annual corrosion rate than other sections.Analysis shows that while the thickness of the material can extend the service life of the tank, the high corrosion rate has the potential to accelerate the failure. The Rooftop is estimated to have a remaining service life of 6.9 years, lower than the rest of the course. This confirms that corrosion management and monitoring are essential to maintain the integrity of the tank and prevent more serious failures. Keywords : Tank, Rooftop, Corrosion, Non-destructive testing